By lepiej słyszeć głos obywateli. Wykorzystanie aplikacji Alertownik w gminie Tarnowo Podgórne w latach 2015-2020 = So that one could hear better the citizens. The use of the Alertownik application in the commune of Tarnowo Podgórne (2015-2020) - Piechocki, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article I present preliminary conclusions from the analysis of the 5-year period use of the Alertownik application in the Tarnowo Podgórne commune. This application has been designed to facilitate precise communication between the Commune Office and the citizen and as such it can be considered as an element of activities facilitating the articulation of the residents? opinions as well as the targeting of informations to them. This should be considered a part of the policy aimed at implementing the idea of a well-informed, active citizens.
Keywords: partycypacja; komunikacja; e-demokracja; participations; communication; e-democracy